EKSISTENSI BAHASA INDONESIA DALAM POLA KOMUNIKASI VERBAL GENERASI Z - Fauziah, Mulya Tiara; Saputra, Desma Yuliadi (Universitas Sultan Ageng Tirtayasa, 2021)
This research aims to analyze the existence of Indonesian in conveying verbal communication among generation Z. The type of research used is descriptive qualitative research in the form of a survey. The subjects of this research were young people belonging to the Z generation group, consisting of 55 respondents. This research will adopt qualitative methods through a qualitative approach, namely using parameters with Google from. This activity will involve direct observation and in-depth interviews with a number of individuals from Generation Z who have diverse social and educational backgrounds in various regions of Indonesia. Qualitative data analysis consists of four activity streams, namely: data collection, data reduction, data presentation, and conclusions. The research results state, (1) The intensity of language use in conveying verbal communication is divided into three parts, namely; (A) The intensity of language use by generation Z is dominated by the use of slang or modified language. This is related to the tendency to express themselves more casually and follow everyday language trends. (B) The intensity of use of standard language or language that is good and correct used by the majority of Generation Z is only at formal events. This is related to self- positioning in an effort to increase the impression of professionalism in formal situations, although there are some who claim to use standard language more often However, it seems that the use of this language has not been fully created in non-formal situations, whereas (C) In formal situations, language choice expresses preferring to use standard language in formal situations and some express it depending on the person they are talking to and a small number choose to use informal language or fail and modifications and mixtures even in formal situations. (2) The ability to communicate verbally, namely speaking and writing using standard language or language that is good and correct, most of generation Z can speak and write using standard language well, others have good abilities in only one of them and a small number not really able to use standard language well and even tend to have little understanding of the use of standard language. (3) The existence of the Indonesian language has evolved over time, there are modified languages made by the younger generation, especially generation Z, and even several modified languages have been added to the KBBI. This also has an impact on the existence of the language, the positive impact is increased knowledge of the language, enjoyable communication and Language inclusivity while the negative impact is the lack of use of standard language, changes in ethics in communication and errors in the use of modified language (slang).